2017
DOI: 10.21760/jaims.v2i05.10275
|View full text |Cite
|
Sign up to set email alerts
|

Ayurvedic management of Retinitis Pigmentosa (Doshandha) - A Case Study

Abstract: Retinitis pigmentosa (RP) is an inherited, degenerative eye disease that causes severe vision impairment due to the progressive degeneration of rod photoreceptor cells in retina. This form of retinal dystrophy manifests initial symptoms independentof age; thus, RP diagnosis occurs anywhere from early infancy to late adulthood. This primary pigmentary retinal dystrophy is a hereditary disorder predominantly affecting the rods more than the cones. The main classical triads of retinitis pigmentosa are arteriolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…1. A clinical case study on RP adopted treatment protocol including Seka with Triphala and Yashti Kashaya, Aschyotana and Tarpana with Jivantyadi Ghrita, oral medication like Saptamrutaloha and Triphala Ghrita reported that visual acuity of patient was stabilized by this management [41]. 2.…”
mentioning
confidence: 99%
“…1. A clinical case study on RP adopted treatment protocol including Seka with Triphala and Yashti Kashaya, Aschyotana and Tarpana with Jivantyadi Ghrita, oral medication like Saptamrutaloha and Triphala Ghrita reported that visual acuity of patient was stabilized by this management [41]. 2.…”
mentioning
confidence: 99%